Problems and prospects of the development of interaction between government bodies and non-governmental organizations of the Republic of Kazakhstan - Dontsov, S.S. (BUKETOV BUSINESS REVIEW, 2019)
In the article the ways to optimize the interaction of state bodies and non-governmental organizations (NGOs) of the Republic of Kazakhstan are discussed. The concept and main goals of NGOs in modern conditions were defined. The most important sociopolitical factors causing the need for interaction between NGOs and the state, as well as the basic principles of interaction of NGOs with government bodies were listed. A set of laws of the Republic of Kazakhstan regulating the interaction of NGOs with government bodies was given. The list of central state bodies of the Republic of Kazakhstan implementing state social order for NGOs was determined, its volume and structure were investigated. The current state of the domestic NGO sector was analyzed from the point of view of government agencies and NGOs. The structure of Kazakhstan’s NGOs was studied taking into account their organizational and legal forms and regions of the Republic of Kazakhstan. The experience of our NGOs and the range of services they provide to their target audience was studied. The structure of funding sources for NGOs' activities, as well as the factors causing the increase or reduction of their target audience were analyzed. Sectoral state structures with which NGOs have the most trusting relations and active cooperation were determined. A number of problematic issues and barriers that impede the development of non-governmental organizations and their interaction with government bodies were identified. Solutions to problematic issues were proposed, including in the field of support for rural NGOs and their initiatives. A detailed analysis of the situation was given regarding NGOs, current trends and their further development prospects.